Safety assessment of external defects in the nozzle-head intersection of a nuclear steam generator. (October 2022) - Tan, Jian-Ping; Zhang, Rui-Kai; Li, Yue; Zeng, Xin; Liu, Pan; Wang, Da-Sheng; Jin, Ting
Abstract: The nozzle-head intersection of a nuclear steam generator (SG) has gained great attention due to its special location and prone to cracks. For the purpose of estimating and ensuring the integrity of the SG structure, the fracture evaluation of nozzle-head intersection after a period of operation needs to be analyzed under a variety of loading conditions. In this paper, stress intensity factors (SIFs) of external surface cracks postulated at the nozzle-head intersection of a SG subjected to pressure, bending, and thermal loadings are evaluated using finite element method. Comparing to the SIFs of cracked pipe described in the RSE-M code, it is found that SIF calculation method of cracked pipe can be conservatively applied to the external surface cracks at the nozzle-head intersection of the SG. Using the conservative SIF solution, the fatigue crack growth and fracture assessment of the postulated cracks are evaluated according to the RSE-M code considering the material aging. Finally, the critical crack size and allowable initial crack size for the life of 40 years are given for the nozzle-head intersection of the SG. Highlights: The SIF solution of pipe in RSE-M can be conservatively used to the external surface cracks at the nozzle-head intersection. The initial size of a *2 c  = 10*30 mm will be unsafefor 40 years life with RT NDT = 50 °C using the conservative method. The conservative critical crack size and allowable initial crack size are given for the life of 40 years with various RT NDT .